Relatedness of Helicobacter pylori populations to gastric carcinogenesis - Dong, Quan-Jiang (Baishideng Publishing Group Co., Limited, 2012)
Helicobacter pylori (H. pylori) is a Gram-negative bacterium that infects half of the human population. The infection is associated with chronic inflammation of the gastric mucosa and peptic ulcers. It is also a major risk factor for gastric cancer. Phylogenetic analysis of global strains reveals there are seven populations of H. pylori, including hpAfrica1, hpAfrica2, hpEastAsia, hpEurope, hpNEAfrica, hpAsia2 and hpSahul. These populations are consistent with their geographical origins, and possibly result from geographical separation of the bacterium leading to reduced bacterial recombination in some populations. For each population, H. pylori has evolved to possess genomic contents distinguishable from others. The hpEurope population is distinct in that it has the largest genome of 1.65 mbp on average, and the highest number of coding sequences. This confers its competitive advantage over other populations but at the cost of a lower infection rate. The large genomic size could be a cause of the frequent occurrence of the deletion of the cag pathogenicity island in H. pylori strains from hpEurope. The incidence of gastric cancer varies among different geographical regions. This can be attributed in part to different rates of infection of H. pylori. Recent studies found that different populations of H. pylori vary in their carcinogenic potential and contribute to the variation in incidence of gastric cancer among geographical regions. This could be related to the ancestral origin of H. pylori. Further studies are indicated to investigate the bacterial factors contributing to differential virulence and their influence on the clinical features in infected individuals.